Assembly of a di-cobalt(II) substituted sandwich-type molybdovanadate with magnetic properties and bifunctional electrocatalytic activities. Issue 14 (18th July 2018) - Gao, Qiao; Lin, Zhe; Duan, Minghua; Li, Dehui; Li, Xiaohua; Wu, Yong; Hu, Donghua
Abstract: A new molybdovanadate, [HN(CH3 )3 ]10 [Co2 (VMo9 O33 )2 ]·8H2 O (1 ) was synthesized by a conventional self-assembly reaction in aqueous solution and structurally characterized by elemental analysis, IR spectra, UV electronic spectroscopy, and X-ray diffraction. Compound1 exhibits a sandwich-type framework based on molybdovanadate anions [VMo9 O33 ] 7− linked by a dinuclear cobalt(II) cluster, which is a first observation in a sandwich-type molybdovanadate system. Electrocatalytic experiments show that1 exhibits bifunctional electrocatalytic activities for the oxidation of dopamine (DA) and the reduction of IO3 − . Magnetic measurements of1 indicate the presence of antiferromagnetic interactions between cobalt ions. Abstract :